The Effect of Tax Education on Generation Alpha’s Tax Awareness: An Experimental Study - Osman Geyik; Gamze Yıldız Şeren; Yusuf Yakşi (International Journal of Public Finance)
Tax education in children increases tax awareness. This study aims to increase tax awareness in children through tax education. Children born after 2010, called the alpha generation, were selected as the sample. In this context, a quasi-experimental design with pre-test and post-test comparisons was used to measure and improve tax awareness among 6th, 7th and 8th grade students. In addition, unstructured open-ended interview technique was used. According to the main findings of the study, tax education has positive effects on children's tax awareness. While tax awareness of children was low before tax education, it was observed that tax awareness increased after the education. The level of awareness among female students has improved proportionally more than that among male students. Following tax education, children developed an understanding of the connection between taxes and public services, fostering awareness of the purpose behind tax payments. Students also shifted their descriptions of those who do not pay taxes from 'cunning' to 'thieves'. Additionally, an increase was observed in students' willingness to engage in tax education.